Classification of immature mosquito species according to characteristics of the larval habitat in the subtropical province of Chaco, Argentina - Stein, Marina (2011)
Fil: Stein, Marina. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.